Out-of-pocket and catastrophic expenses in households of patients with schizophrenia lacking social security - Hortensia Reyes-Morales; Héctor Cabello-Rangel; María Elena Medina-Mora; Armando Arredondo-López (Instituto Nacional de Salud Pública, 2021)
Objective. To estimate the magnitude of out-of-pocket (OOP) and catastrophic health expenses as well as impoverishment experienced by households of schizophrenia patients lacking social security coverage. Materials and methods. We conducted a cross-sectional study of 96 individuals treated outpatient consultation between February and December 2018, in a psychiatric hospital. Results. All households sustained OOP health expenses; the median was 510 USD (95%CI: 456-628). The OOP expenses represented 28 and 4% of the capacity to pay of poor and rich households, respectively. The 16% of households incurred catastrophic expenses and 6.6% have impoverishment for health reasons. Conclusions. Our results illustrate that pocket expenses and catastrophic expenses in patients with schizophrenia are higher than those reported for the general population. Therefore, it is necessary to rethink the financial protection policies aimed at patients with schizophrenia and their households.